One-dimensional diamondoid polyaniline-like nanothreads from compressed crystal aniline - Nobrega, Marcelo M. (Chem Sci, 2017)
Low-dimensional nanomaterials such as highly ordered polyaniline (PANI) have attracted considerable interest due to their expected extraordinary electronic and optoelectronic properties. In spite of several attempts, the attainment of atomically well-ordered PANI is a long-standing challenge. Pressure-induced polymerization of aromatic molecules in the crystal phase has been demonstrated as a practicable route for the synthesis of highly ordered polymers but this approach has never been tested to produce PANI. Here we show the synthesis of diamondoid polyaniline-like nanothreads at 33 GPa and 550 K by compressing aniline in crystal phase-II. Infrared spectroscopy, transmission electron microscopy, X-ray diffraction data, and DFT calculations support the formation of this totally new polyaniline-like nanothread. The NH(2)-enriched carbon nanothread combines the outstanding mechanical properties of carbon nanotubes with the versatility of NH(2) groups decorating the exterior of the nanothreads representing potential active sites for doping and as linkers for molecules with biological interest and inorganic nanostructures. The synergy of all of these properties emphasizes the strong potential of this material to be applied in a broad range of areas, from chemistry to materials engineering.